Carbon Ion Therapy Inhibits Esophageal Squamous Cell Carcinoma Metastasis by Upregulating STAT3 Through the JAK2/STAT3 Signaling Pathway - Luo, Hongtao; Yang, Zhen; Zhang, Qiuning; Shao, Lihua; Wei, Shihong; Liu, Ruifeng; Li, Zheng; Geng, Yichao; Li, Chengcheng; Wang, Xiaohu (Frontiers in Public Health, 2020)
Radiation therapy is an important component of the comprehensive treatment of esophageal cancer. However, conventional radiation resistance is one of the main reasons for treatment failure. The superiority of heavy ion radiation in physics and biology has been increasingly highlighted in radiation therapy research. The Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) pathway plays an important role in the occurrence, development and metastasis of esophageal squamous cell carcinoma (ESCC) and is related to the development of resistance to ionizing radiation in ESCC. Therefore, the aim of the present study was to investigate the relationship between carbon ion inhibition of the proliferation and metastasis of esophageal carcinoma cells and the JAK2/STAT3 signaling pathway. The results demonstrated that carbon ion beams significantly reduced cell viability and stimulated apoptosis in human ESCC cells in a dose-dependent manner. In addition, carbon ion beams induced G2/M phase cell cycle arrest in ESCC cells and inhibited tumor metastasis in a dose-dependent manner. Additionally, poorly differentiated KYSE150 cells were more sensitive to the same carbon ion beam dose than moderately differentiated ECA109 cells. Carbon ion beam exposure regulated the relative expression of metastasis-related molecules at the transcriptional and translational levels in ESCC cells. Carbon ion beams also regulated CDH1 and MMP2 downstream of the STAT3 pathway and inhibited ESCC cell metastasis, which activated the STAT3 signaling pathway. This study confirmed the inhibition of cell proliferation and the metastatic effect of carbon ion beam therapy in ESCC cells.